Safety and accuracy of a new long-term subconjunctival glucose sensor - Hasslacher, Christoph; Auffarth, Gerd U.; Rabsilber, Tanja Marina; Kulozik, Felix (Journal of diabetes, 2012)
Background: A new biosensor has been developed by EyeSense (Großostheim, Germany) that is placed into the conjunctiva of one eye to measure the glucose concentration of the surrounding tissue in a non-invasive manner. In the present study we investigated the correlation between glucose concentrations measured by the EyeSense implant and those determined by finger prick testing, as well as the tolerability and safety of the implant over a 16-week period. Methods: The study was performed in 28 diabetic patients. The biosensor was inserted under local anesthesia and sterile conditions. Correlations between capillary glucose measured by laboratory methods and interstitial glucose determined by the biosensor were investigated by inducing increases and decreases in glucose values between 60 and 300 mg/dL. Results: Most patients experienced a mild subconjunctival hemorrhage postoperatively. Except for the minor sensation of the presence of foreign body, the implants were well tolerated. Three patients lost the ocular mini insert spontaneously, whereas there was a function failure of the insert in four patients. Error grid analysis showed that the percentage of data pairs in the acceptable ranges (zone A and B) was very high (>96%). However, there was a shift from zone A to zone B during observation. This was due primarily to an increase in the lag time between capillary and interstitial measured glucose. Conclusion: The present study demonstrates good tolerability and measurement performance of the biosensor. The reasons for an increase in the lag time are still unknown; local reactions may be involved.